Kapasitas Peningkatan Populasi Ternak Sapi Bali di Kecamatan Mowila Kabupaten Konawe Selatan - Abadi, Musram; Saili, Takdir; Hijrawati, Hijrawati; Rizal, Abdul (Musamus University, 2021)
The aim of this research is to study the Capacity to Increase the Population of Bali Cattle in Mowila District, South Konawe Regency. The data used in this study is divided into two, namely, primary and secondary data. Primary data were obtained from surveys and direct interviews with respondents. Meanwhile, secondary data was obtained from related agencies such as the Livestock Service Office, Agriculture Service Office and BPS Konawe Selatan Regency. The variable measured is the Capacity for Increasing the Population of Ruminant Livestock which is analyzed using the calculation of the Capacity for Increasing the Population of Ruminant Livestock. Respondents are Balinese cattle breeders who have 2 or more cattle. The sample was selected from the population by a simple random method, from 10 determined villages/kelurahan, respondents were selected using the Slovin formula with the number of farmer households (RTP) 1,009 and the results obtained were 91 people which were then adjusted by the researchers to 100 people. The results of the research that have been carried out show that Mowila District, Konawe Selatan Regency has the potential to add Bali cattle. This is supported by the availability of human resources, the experience of farmers, the scale of ownership that can be increased, the average farmer already has education and the availability of land.